2019
DOI: 10.1038/s41396-019-0347-6
|View full text |Cite
|
Sign up to set email alerts
|

Functional annotation of orthologs in metagenomes: a case study of genes for the transformation of oceanic dimethylsulfoniopropionate

Abstract: Dimethylsulfoniopropionate (DMSP) is produced mainly by phytoplankton and bacteria. It is relatively abundant and ubiquitous in the marine environment, where bacterioplankton make use of it readily as both carbon and sulfur sources. In one transformation pathway, part of the molecule becomes dimethylsulfide (DMS), which escapes into the atmosphere and plays an important role in the sulfur exchange between oceans and atmosphere. Through its other dominant catabolic pathway, bacteria are able to use it as sulfur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 65 publications
(83 reference statements)
1
27
0
Order By: Relevance
“…However, the enzymes that catalyze DHPS synthesis are still unknown. All cyanobacteria were believed to lack dmdA gene (González et al, 2019), however, they can take up and assimilate DMSP via an as-yet-unidentified pathway (Malmstrom et al, 2005). In addition, the enzymatic or chemical mechanisms of DMSOP synthesis in DMSP and DMS cycling remained unclear (Thume et al, 2018).…”
Section: Characterizations Of Substrates and Specific Enzymesmentioning
confidence: 99%
“…However, the enzymes that catalyze DHPS synthesis are still unknown. All cyanobacteria were believed to lack dmdA gene (González et al, 2019), however, they can take up and assimilate DMSP via an as-yet-unidentified pathway (Malmstrom et al, 2005). In addition, the enzymatic or chemical mechanisms of DMSOP synthesis in DMSP and DMS cycling remained unclear (Thume et al, 2018).…”
Section: Characterizations Of Substrates and Specific Enzymesmentioning
confidence: 99%
“…These differences may confound ecological studies which aim to predict functional properties of microbial communities from the presence or absence of specific genes. For instance, the presence of dmdA, the first gene in the pathway, is often used to imply the presence of an active demethylation pathway (31,32). However, the presence of this gene is inherently ambiguous.…”
Section: Discussionmentioning
confidence: 99%
“…We know that there are likely other DMSP lyases to be identified in bacteria, since Liu et al (2016) identified bacteria from East China Sea seawater with DMSP lyase activity, but which lack known ddd and Alma1 genes (Liu et al, 2018). In contrast, González et al (2019) considered it would be highly unlikely to find an environmentally significant alternative enzyme to DmdA that would carry out the DMSP demethylation reaction. Further work involving process measurements from hydrothermal samples is required to determine if DMSP cleavage and/or demethylation is an important process in this environment, but these data indicate they are not.…”
Section: The Okinawa Trough Hydrothermal Field Has Its Own Specific Dmentioning
confidence: 99%